Prediction of Adverse effects of Geomagnetic storms and Energetic Radiation (PAGER) project - Yuri Y. Shprits; Tony Arber; Michael Liemohn; Ondřej Santolík; Keith Bennett; Stefano Bianco; Melanie Burns; Angelica Castillo; Marina García Peñaranda; Bernhard Haas; Julia Himmelsbach; Artem Smirnov; et al. (Advances in Space Research, 2026)

Principal results of the Portoviejo (Ecuador) seismic microzonation project and importance for seismic hazard mitigation - Michael Schmitz; Hugo Yepes; Julio J. Hernández; Luis Yegres; André Singer; Luz M. Rodríguez; Duilio Marcial; Javier Sánchez-Rojas; Kenny García; Víctor Rocabado; Pablo B. Palacios; José M. Marrero; et al. (Natural Hazards, 2025)
The 2016 Mw7.8 Pedernales earthquake caused extensive damage along the central Ecuadorian coastline, resulting in 661 casualties, 4859 injured and the collapse of numerous buildings. The city of Portoviejo (Ecuador), located 140 km from the epicenter, was one of the most severely impacted municipalities with approximately 10% of its buildings damaged and 40 reinforced concrete buildings in the city center collapsed. A seismic microzonation study was conducted in Portoviejo to better understand the damage distribution and guide reconstruction efforts and future engineering projects. Based on a seismic hazard assessment and through equivalent linear analyses of multiple soil profiles integrating geological, geotechnical, and geophysical investigations, the study revealed that local conditions significantly influenced seismic ground motion. Specifically, the low Vs30 values, in the valley generally between 225 and 180 m/s, and even lower in some areas, played a critical role. Additionally, these conditions, associated with fluviomarine sandy deposits, contributed to induced effects such as soil liquefaction, which was a key factor in structural damage and infrastructure failure. These findings were used as primary criteria for delineating seismic microzones in the flat areas of the valley. The technical results of the seismic microzonation study, including response spectra for seismic microzones and soil liquefaction potential assessment, have been incorporated into municipal codes. While landslide hazard in Portoviejo is generally low, the risk could increase under extreme events. This integration has enhanced the city’s understanding of its natural environment and contributed to seismic risk mitigation efforts introducing site-specific parameters in the local building code.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Parasitoid avoidance of intraguild predation drives enemy complementarity in a multi‐trophic ecological network - Andrew B. Hennessy; Riley M. Anderson; Nora Mitchell; Kailen A. Mooney; Michael S. Singer (Ecology, 2025)
How consumer diversity determines consumption efficiency is a central issue in ecology. In the context of predation and biological control, this relationship concerns predator diversity and predation efficiency. Reduced predation efficiency can result from different predator taxa eating each other in addition to their common prey (interference due to intraguild predation). By contrast, multiple predator taxa with overlapping but complementary feeding niches can generate increased predation efficiency on their common prey (enemy complementarity). When viewed strictly from an ecological perspective, intraguild predation and enemy complementarity are opposing forces. However, from an evolutionary ecology perspective, predators facing strong intraguild predation may evolve traits that reduce their predation risk, possibly leading to niche complementarity between enemies; thus, selection from intraguild predation may lead to enemy complementarity rather than opposing it. As specialized predators that live in or on their hosts, parasitoids are subjected to intraguild predation from generalist predators that consume the parasitoids' hosts. The degree to which parasitoid–predator interactions are ruled by interference versus enemy complementarity has been debated. Here, we address this issue with field experiments in a forest community consisting of multiple species of trees, herbivorous caterpillars, parasitoids, ants, and birds. Our experiments and analyses found no interference effects, but revealed clear evidence for complementarity between parasitoids and birds (not ants). Parasitism rates by hymenopterans and dipterans were negatively associated with bird predation risk, and the variation in the strength of this negative association suggests that this enemy complementarity was due to parasitoid avoidance of intraguild predation. We further argue that avoidance of intraguild predation by parasitoids and other arthropod predators may explain enigmatic patterns in vertebrate–arthropod–plant food webs in a variety of terrestrial ecosystems.

Melt inclusions in zircon: a window to understanding the structure and evolution of the magmatic system beneath the Laguna del Maule volcanic field - Kei Shimizu; Tyler B. Blum; Chloe E. Bonamici; John H. Fournelle; Christine E. Jilly-Rehak; Noriko T. Kita; Kouki Kitajima; Jacob D. Klug; Will O. Nachlas; Brad S. Singer; Michael J. Spicuzza; Alexander V. Sobolev; et al. (Contributions to Mineralogy and Petrology, 2024)

A river runs through it: Robust automated mapping of riparian woodlands and land surface phenology across dryland regions - Conor A. McMahon; Dar A. Roberts; John C. Stella; Anna T. Trugman; Michael B. Singer; Kelly K. Caylor (Remote Sensing of Environment, 2024)

Correction to Migrating Ducks and Submersed Aquatic Vegetation Respond Positively After Invasive Common Carp (Cyprinus carpio) Exclusion from a Freshwater Coastal Marsh - Lauren E. Bortolotti; Robert B. Emery; Paige D. Kowal; Llwellyn M. Armstrong; Vanessa B. Harriman; Howard V. Singer; Michael J. Anteau; Frank B. Baldwin; Cameron Meuckon; Dale A. Wrubleski (Wetlands, 2023)

Migrating Ducks and Submersed Aquatic Vegetation Respond Positively After Invasive Common Carp (Cyprinus carpio) Exclusion from a Freshwater Coastal Marsh - Lauren E. Bortolotti; Robert B. Emery; Paige D. Kowal; Llwellyn M. Armstrong; Vanessa B. Harriman; Howard V. Singer; Michael J. Anteau; Frank B. Baldwin; Cameron Meuckon; Dale A. Wrubleski (Wetlands, 2023)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Progressive brain atrophy in chronically infected and treated HIV+ individuals - Talia M. Nir; Neda Jahanshad; Christopher R. K. Ching; Ronald A. Cohen; Jaroslaw Harezlak; Giovanni Schifitto; Hei Y. Lam; Xue Hua; Jianhui Zhong; Tong Zhu; Michael J. Taylor; Thomas B. Campbell; et al. (Journal of NeuroVirology, 2019)

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Erratum to: Characterization of Pharmacokinetics in the Göttingen Minipig with Reference Human Drugs: An In Vitro and In Vivo Approach - Floriane Lignet; Eva Sherbetjian; Nicole Kratochwil; Russell Jones; Claudia Suenderhauf; Michael B. Otteneder; Thomas Singer; Neil Parrott (Pharmaceutical Research, 2016)

Characterization of Pharmacokinetics in the Göttingen Minipig with Reference Human Drugs: An In Vitro and In Vivo Approach - Floriane Lignet; Eva Sherbetjian; Nicole Kratochwil; Russell Jones; Claudia Suenderhauf; Michael B. Otteneder; Thomas Singer; Neil Parrott (Pharmaceutical Research, 2016)

Factors related to HIV-associated neurocognitive impairment differ with age - Gary B. Fogel; Susanna L. Lamers; Andrew J. Levine; Miguel Valdes-Sueiras; Michael S. McGrath; Paul Shapshak; Elyse J. Singer (Journal of NeuroVirology, 2015)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Inbreeding depression and the maintenance of genetic load in Melitaea cinxia metapopulations - Sari Haikola; Wilhelm Fortelius; Robert B. O'Hara; Mikko Kuussaari; Niklas Wahlberg; Ilik J. Saccheri; Michael C. Singer; Ilkka Hanski (Conservation Genetics, 2001)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)